2018
DOI: 10.1177/1099636218789613
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of moisture effects on novel agglomerated cork core sandwich composites with fiber metal laminate facesheets

Abstract: A sandwich material would be an attractive structural candidate for marine applications as long as it can retain its environmental durability. However, the susceptibility to moisture attacks is still the major drawback of sandwich materials in comparison to the single skin laminates. Hence, this paper aims to study the effect of moisture absorption on the mechanical behavior of a newly developed sandwich structure, which is intended for use as a water-resistant constructive system in marine industries. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…It is well known that when polymer nano-composites (PNCs) are immersed in water or exposed to moisture, moisture gradually penetrates to the polymer and may adversely affect the properties of the composite. [14][15][16] Katnam et al 17 studied the effect of moist environment on the static and fatigue behaviors of rubber-toughened epoxy adhesive. Results indicated that both the static and fatigue resistances of adhesively bonded joints are considerably affected by the moisture absorption.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that when polymer nano-composites (PNCs) are immersed in water or exposed to moisture, moisture gradually penetrates to the polymer and may adversely affect the properties of the composite. [14][15][16] Katnam et al 17 studied the effect of moist environment on the static and fatigue behaviors of rubber-toughened epoxy adhesive. Results indicated that both the static and fatigue resistances of adhesively bonded joints are considerably affected by the moisture absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning work environment, some studies wondered about the harsher conditions that agglomerated cork sandwich structures may face when employed in marine environment thus assessing the effect of water absorption [46,131] and salt fog exposure [132,133] on their quasistatic and dynamic response. It must be considered that cork enclosure between skin laminates tends to reduce water uptake and the exposure to salt fog, but impact events can cause skin damage and perforation phenomena which can imply a direct exposure of the core to the work environment.…”
Section: Novelty and Implicationsmentioning
confidence: 99%
“…Although the experimental works have been done on the moisture diffusion behaviors of sandwich structures [19][20][21][22], few analytical works have been done to describe their moisture diffusion behaviors, especially for sandwich structures which have a multiphase structure. Yu and Zhou [23] studied two-phase moisture diffusion equations for the moisture diffusion behaviors of flax/glass fiber reinforced composites.…”
Section: Introductionmentioning
confidence: 99%